Comparative Analysis of Drug Policy Prices and National Procurement Systems in Universal Health Coverage - Erlisa Irawati Putri; Chairun Wiedyaningsih; Roshinta Andien Damayanti (Journal of Health Economic and Policy Research (JHEPR), 2026)
Background: Access to affordable essential medicines is a key prerequisite for achieving Universal Health Coverage (UHC), particularly in developing countries facing fiscal pressures and pharmaceutical market inefficiencies. However, the effectiveness of medicine pricing policies varies significantly between countries, depending on regulatory design, procurement capacity, and political commitment to universal access. Aims: This study aims to analyse and compare drug pricing policies and national procurement systems in five Asian countries—Indonesia, the Philippines, Thailand, Malaysia, and India—in the context of UHC. Methods: This study employs a comparative policy analysis approach, utilising secondary data from national regulations, official government reports, and academic literature. Results: Thailand has demonstrated the most effective model, combining HTA, compulsory licensing, and a centralized GPO system, which reduces drug prices by up to 90%. India optimises generic procurement through the Jan Aushadhi programme, while Malaysia combines external price references with tiered enforcement policies. In contrast, Indonesia and the Philippines still face challenges in price compliance and distribution efficiency, due to institutional fragmentation and weak oversight. Conclusion: This study underscores the importance of integrating robust regulatory strategies, effective procurement mechanisms, and rigorous monitoring systems to ensure affordability and equitable access to medicines. Cross-country learning can strengthen national pharmaceutical reforms and support policy integration in the ASEAN region. Keywords: Drug prices, UHC, pharmaceutical procurement, Asian pharmaceutical policy.